Answer:
[tex]y=(\frac{-3}{2} )x + 5[/tex]
Step-by-step explanation:
Only one thing you have to remember here and it is the equation for a linear line. This equation is:
[tex]y-y_{0} = m(x-x_{0})[/tex]
Where m is the slope:
[tex]m=\frac{dy}{dx} =\frac{y_{2}-y_{1} }{x_{2} -x_{1} }[/tex]
Writing the whole thing out using the given data points we get:
[tex]y-8=\frac{(-1)-8}{4-(-2)} (x-(-2))[/tex]
We then just have to equate this to an equation of the form y = mx + b:
⇒ [tex]y=\frac{-9}{6} (x+2) + 8[/tex]
⇒ [tex]y=(\frac{-3}{2} )x+ (\frac{-3}{2})2 + 8[/tex]
⇒ [tex]y=(\frac{-3}{2} )x + (-3) + 8[/tex]
⇒ [tex]y=(\frac{-3}{2} )x + 5[/tex]
And there we go, our equation has been found.